Strategi Upscaling UMKM pada Era Marketing 5.0 - Riptiono, Sulis (LP3M Universitas Putra Bangsa, 2022)
MSMEs are one of the most important pillars in the Indonesian economy by contributing to the national GDP in the range of 61 percent and absorbing 97 percent of the total workforce. Even in every crisis period, MSMEs even become buffers, are resilient, and can recover well. Thus, the purpose of this community service is to provide motivation and knowledge to MSME actors in Kebumen to increase their business level in the marketing 5.0 era. This activity involved 25 entrepreneurs held at the Integrated Business Service Center. Marketing strategy is very important in a business. In this digital era, entrepreneurs must adapt to the changes that occur. Therefore, participants are expected to be able to increase their business level in the marketing 5.0 era